Efektivitas Penerapan UU No. 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual dalam Penanganan Kasus Penyebaran Konten Intim Tanpa Izin (Non-Consensual Intimate Images) di Indonesia - Ramadhany Nasution (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2026)
The spread of Non-Consensual Intimate Images (NCII) has become one of the most damaging forms of technology-based sexual violence in Indonesia. Komnas Perempuan data consistently shows a year-on-year rise in gender-based online violence reports, while SAFEnet documented hundreds of NCII cases between 2017 and 2023. Before Law Number 12 of 2022 on the Crime of Sexual Violence (TPKS Law) was enacted, Article 27 paragraph (1) of the Electronic Information and Transactions Law (ITE Law) was the only legal basis for handling NCII — a provision that frequently revictimized survivors rather than protecting them. This study examines: (1) how NCII is regulated under the TPKS Law; and (2) the effectiveness of the TPKS Law in addressing NCII cases, analyzed through Lawrence M. Friedman's three-component theory of legal effectiveness: legal substance, legal structure, and legal culture. Normative legal research was applied using statutory, conceptual, and analytical approaches. The study finds that Article 14 of the TPKS Law provides a substantially stronger and more victim-centred legal basis than previous regulations. However, effectiveness is still hampered by inadequate law enforcement capacity, uneven availability of integrated service units (UPTD PPA), low survivor reporting rates linked to persistent stigma, and a pervasive victim-blaming culture. Law reform alone is insufficient; structural and cultural transformation must accompany it.